Using Communication Technology to Enhance Interprofessional Education Simulations - Shrader, Sarah (Am J Pharm Educ, 2016)
Objective. To determine the impact of simulations using an alternative method of communication on students’ satisfaction, attitudes, confidence, and performance related to interprofessional communication. Design. One hundred sixty-three pharmacy students participated in a required applications-based capstone course. Students were randomly assigned to one of three interprofessional education (IPE) simulations with other health professions students using communication methods such as telephone, e-mail, and video conferencing. Assessment. Pharmacy students completed a validated survey instrument, Attitude Toward Healthcare Teams Scale (ATHCTS) prior to and after course participation. Significant positive changes occurred for 5 out of 20 items. Written reflection papers and student satisfaction surveys completed after participation showed positive themes and satisfaction. Course instructors evaluated student performance using rubrics for formative feedback. Conclusion. Implementation of IPE simulations using various methods of communication technology is an effective way for pharmacy schools to incorporate IPE into their curriculum.